2020
DOI: 10.1002/sctm.19-0423
|View full text |Cite
|
Sign up to set email alerts
|

Killers at the crossroads: The use of innate immune cells in adoptive cellular therapy of cancer

Abstract: Adoptive cell therapy (ACT) is an approach to cancer treatment that involves the use of antitumor immune cells to target residual disease in patients after completion of chemo/radiotherapy. ACT has several advantages compared with other approaches in cancer immunotherapy, including the ability to specifically expand effector cells in vitro before selection for adoptive transfer, as well as the opportunity for host manipulation in order to enhance the ability of transferred cells to recognize and kill establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 121 publications
0
14
0
Order By: Relevance
“…NKT-based clinical trials are ongoing for several malignancies, and are based on the injection of alpha-Galactosylceramide (α-GalCer) or α-GalCer-pulsed APC to expand NKT cells in vivo. Alternatively, autologous NKT cells have been expanded ex vivo using IL-2 and anti-CD3 mAbs [ 94 ]. Recent evidence suggested that NKT cells may have anti-tumor activities in NB patients.…”
Section: Adoptive Cell Therapy Based On Nkt Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…NKT-based clinical trials are ongoing for several malignancies, and are based on the injection of alpha-Galactosylceramide (α-GalCer) or α-GalCer-pulsed APC to expand NKT cells in vivo. Alternatively, autologous NKT cells have been expanded ex vivo using IL-2 and anti-CD3 mAbs [ 94 ]. Recent evidence suggested that NKT cells may have anti-tumor activities in NB patients.…”
Section: Adoptive Cell Therapy Based On Nkt Cellsmentioning
confidence: 99%
“…γδ T cells and NK cells may represent an ideal source for adoptive cell therapy due to some shared features. Both cell types recognize and kill tumor cells irrespective of the expression of a single tumor-associated antigen, thus avoiding tumor immune escape related to single antigen loss [ 67 , 68 , 69 , 94 , 114 , 115 ]. In addition, γδ T and NK cells act through MHC-independent recognition of target cells, thus reducing the risk of alloreactivity and GvHD [ 116 ] and are able to provide immediate release of effector cytokines in different tissues.…”
Section: Future Prospects: Car Nk Cells and γδ T Cellsmentioning
confidence: 99%
“…Adoptive NK cell therapy refers to the introduction of ex vivo manipulated NK cells to patients for clinical use. In malignant diseases, autologous NK cell activity is inhibited largely because of the KIR ligand match, thus conferring limited clinical benefits 43 . However, NK cells from an allogeneic source have offered a promising choice for immunotherapy 44 .…”
Section: Nk Cell-based Immunotherapymentioning
confidence: 99%
“…NK cells have a shorter lifespan and secrete a safer cytokine profile than T cells; therefore, they might decrease the incidence and severity of adverse effects associated with autoimmunity and CRS. However, their limited persistence in vivo has also led to concerns regarding their potential efficacy 43 .…”
Section: Nk Cell-based Immunotherapymentioning
confidence: 99%
“…N atural killer cells are powerful effector cells in the anticancer immune response and act via direct recognition and killing of tumor cells, promotion of adaptive immune responses, and Ab-dependent cellular cytotoxicity (ADCC) (13). There is intense interest in targeting NK cells for cancer therapy via adoptive cellular therapies as well as via Ab-and cytokine-mediated stimulation (1,3,4).…”
mentioning
confidence: 99%